EFFICIENCY OF THE RENEWABLE ENERGY SOURCES APPLICATION FOR AN AUTONOMOUS HEAT SUPPLY SYSTEM - Viktor Denysov (General Energy Institute of the National Academy of Sciences of Ukraine, 2023)
Description of the developed software and information complex for modeling autonomous heatsupply systems provided, which allows optimizing the selection of units and their operation modes andensuring the production and redistribution of thermal energy in accordance with the scheduleof consumers. Optimized modes simulation operation of the autonomous heat supply system for a cottagevillage based on local energy resources with minimal use of external energy sources performed. The useof software and information complex made it possible to calculate the parameters that provide optimalcoverage of the heat load schedule of a cottage settlement based on local energy resources. Forthe calculation, the predicted values of the installed thermal power of the units and the heat load graphwhich was obtained by adapting the real annual graph of the external temperature of Stockholm tothe geographical location of the Kyiv region were used. The developed new software and informationcomplex provide an opportunity for hourly modeling, research into the optimal modes of operationof heat units, and evaluation of the effectiveness of the use of renewable energy sources in autonomousheat supply systems. In the developed software and information complex, the model of optimizationof operating modes is applied, which belongs to the class of problems of optimal loading of generatingcapacities of power systems with the criterion of minimizing costs for production, accumulation, andconsumption of thermal energy. An example of simulation results using a heat load schedule fora selected typical day is presented. The obtained results indicate a decrease in the specific cost of hourlyheat supply with an increase in the part of thermal energy supplied at the expense of renewable energysources. This is due to a decrease in the share of gas, and in general, any other generation basedon fossil fuel technologies, in the total volume of heat supply. Thus, the effectiveness of the useof renewable energy sources based on local energy resources as part of the heat supply system ofthe cottage village was confirmed.